Biochemical profiling of tetraploid potato (Solanum tuberosum) genotypes - SINGH, JAGMEET; KUMAR, DHARMINDER; BHARDWAJ, VINAY; SOOD, SALEJ; DAROCH, RAKESH KUMAR (The Indian Journal of Agricultural Sciences, 2024)
An experiment was conducted out during winter (rabi) seasons of 2021–22 and 2022–23 at Litchi and Mango Research Station (Dr. Y S Parmar University of Horticulture and Forestry, Solan, Himachal Pradesh), Nagrota Bagwan, Kangra, Himachal Pradesh to study the biochemical profiling of tetraploid potato (Solanum tuberosum L.) genotypes. The experiment comprises of 357 genotypes including varieties, advanced breeding lines and exotic germplasm belonging to the tetraploid group of potato were evaluated in augmented block design. Data were recorded on different biochemical attributes. Adjusted mean values indicated that CP 3145 (10.15ᵒBrix) for total soluble solids, CP 1689 (36.89 mg/g) for total polyphenols, CP 1302 (28.68 mg/100 g) for ascorbic acid, CP 3891 (24.41 µg/g) for total carotenoids content, CP 1667 (0.21%,) for total sugars, CP 1667 (0.10%) for reducing sugars and CP 1884 (0.06%) for non-reducing sugars were the top ranked genotypes. High PCV and GCV were observed for total polyphenols and total carotenoids content. High heritability coupled with high genetic advance was recorded for total polyphenols, ascorbic acid content, starch content, total carotenoids content and reducing sugars. Principal component analysis indicated the three most informative principal components with more than one eigen value, accounting for 57.40% of the total variance for all traits.